Studying structural characteristics of Saqez–Takab Region (NW of Sanandaj–Sirjan Zone) using GiT (Geoinformation Techniques) - Haji, Erfan; Safari, Hojjatollah; Bafti, Behnam Shafiee; Atabay, Maryam Agh (Sulaimani Journal for Pure and Applied Sciences, 2016)
Saqez–Takab Region, as the northwestern part of Sanandaj–Sirjan deformed and metamorphosed Zone (NW part of Zagros Fold and Thrust belt, NW of Iran) has been studied in this research for detection of structural characteristics and tectonic evolution. Based on the prepared lineament map, all faults (lineaments) can be classified to 3 different sets by their length values: the Major, Main and Minor Faults. Eastern part of the study region is the least populated area by both the number and the length values of measured faults. The faults with E-W strike trends are formed in the east and central east, NW-SE trending faults are situated in the north-west and central west, and NE-SW trending faults can be seen in the south-western part of the region. By analyzing the faults kinematics, containing fault planes and P-Axis values there are at least 3 main structural generations. Based on comparison of the strike values of outcropped faults, fault plane orientations, P-Axes values (directions), observed lateral displacement relationships and the other evidences the oldest fault set is oriented N135 (ductile condition /shear zone) and is dextral. The younger set is N70 (brittle – ductile condition) with both sinistral and reverse slipping; and the youngest one has a mean direction of N15 (brittle condition) with a sinistral movement. These last movements of the 3 old fault systems are related to the final deformation phases of Saqez – Takab Region.
Keywords: SaqezTakab RegionGiT TechniquesRS MethodsKinematic AnalysisIsofracture MapFault Classification